PREPARATION AND EVALUATION OF VORICONAZOLE HYDROGEL USING CYCLODEXTRIN-BASED NANO SPONGES - MD APSAR PASHA; SEEMA TOMAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This project aimed to develop a cyclodextrin-based nanosponge (CDNS) gel for topical skin application to enhance the therapeutic efficacy, distribution, and stability of voriconazole (VO). The focus was on improving drug release, skin penetration, and antifungal activity while preventing VO’s photodegradation and chemical degradation. Methods: CDNS was prepared by crosslinking cyclodextrins with diphenyl carbonate using convection heating. VO-loaded nanosponges (VONS) were freeze-dried and incorporated into a hydrogel formulation with Carbopol 974, propylene glycol, and ethanol, optimized through Box-Behnken design. Procedural parameters and quality attributes were analyzed using statistical tools like analysis of variance. The formulation was characterized by Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and X-ray diffraction (XRD) to confirm the inclusion complex formation. Particle size, polydispersity index, zeta potential, and encapsulation efficiency were evaluated. Transmission electron microscopy (TEM) was used to assess the nanosponges’ morphology. Results: Optimized VONS exhibited particle sizes of 50–75 nm with minimal polydispersity, ensuring uniform distribution. High zeta potential values confirmed stability and low agglomeration. FTIR, DSC, and XRD confirmed the formation of inclusion complexes, while TEM revealed spherical nanoparticles. The encapsulation efficiency was high, enhancing drug loading. In vitro studies showed faster drug release from VONS compared to pure VO. Topical hydrogels (VONS2, VONS8, and VONS12) exhibited controlled drug release and superior skin penetration over 12 h. The formulation prevented VO photodegradation and chemical degradation for up to 6 months, with significant improvements in antifungal efficacy and stability. Conclusion: The developed CDNS gel demonstrated controlled drug release, enhanced skin penetration, and superior storage stability, making it a promising strategy for improving VO’s therapeutic impact in topical applications. The formulation successfully addressed challenges like photodegradation, chemical degradation, and low skin permeability.